Sensitivity of the sea level change to model resolution in Max Planck Institute Earth System Model (MPI-ESM) simulations - Wickramage, Chathurika Hemamali (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2023)
Rising sea level driven by global warming is a serious threat to the coastal communities whose livelihoods depend on the coastal ecosystem. Hence, effective adaptation measures are needed to mitigate the predicted dangers of sea level rise. To be able to make informed decisions and develop successful adaptation strategies, accurate and reliable sea-level projections are essential for the coming decades. However, current climate models do not have the resolution to explicitly represent mesoscale processes in the ocean component; as a result, these processes are parameterized. The limited description of mesoscale processes in these models results in systematic errors in simulating ocean circulation properties, affecting the accuracy of sea-level projections. To study the dependence of future sea-level change on ocean model resolution, the dynamic sea level (DSL; sea surface height above the geoid) change patterns in a climate model featuring an eddy rich ocean component are compared to those of state-of-the-art coarser resolution versions of the same model. The study examines the impact of spatial resolution on sea level projections using Max Planck Institute Earth System Model (MPI-ESM) simulations. Three different spatial resolutions are taken into consideration: low resolution (LR) of about 1.5°, high resolution (HR) of 0.4°, and eddy-rich resolution (ER) of 0.1°. In the first part, the DSL changes for each configuration are analyzed by comparing the time mean of the SSP5-8.5 climate change scenario for the years 2080–2099 to the time mean of the historical simulation for the years 1995–2014. The ER model, which resolves mesoscale processes, projects a higher DSL increase in the North Atlantic sub-polar region, the Kuroshio region, and the Arctic Ocean compared with models with parameterized eddies (HR and LR). In addition, a smaller DSL increase is observed in the band at 40°S in the Southern Ocean, compared to HR and LR models. The differences between the two model categories, in these regions, can be ...